The ranking of fungi: a tribute to David L. Hawksworth on his 70th birthday - Kevin D. Hyde (2018)
© 2017, School of Science. The history of assigning ranks to fungi, as well as the relative importance of using divergence time estimates is reviewed. The paper pays tribute to the major mycological players, and especially to David Hawksworth on his 70th birthday and his contribution to fungal ranking in Systema Ascomycetum from 1982 to 1998. Following the conclusion of the latter series, the ranking continued with the Outlines of Ascomycota in 2007 and 2010 and more recently with specific classes in ‘Towards an outline of Sordariomycetes’ and ‘Families of Dothideomycetes’. Earlier classifications based on phenotype were certainly more subjective; however, remarkably many of these old arrangements have stood the test of time. More recently, phylogenetic analyses have provided evidence towards a natural classification, resulting in significant changes in many lineages. The classification arrangements however, are still subjective and dependent on the taxa analysed, resulting in different taxonomic interpretations and schemes, particularly when it comes to ranking. Thus, what have been considered as genera by some, have been introduced as families by others. More recently, estimation of divergence times using molecular clock methods have been used as objective evidence for higher ranking of taxa. A divergence period (i.e. 200–300 MYA) can be used as a criterion to infer when a group of related taxa evolved and what rank they should be given. We compiled data on divergence times for various higher ranking taxa in the Kingdom Fungi. The kingdom evolved 1000–1600 MYA (Stenian–Calymmian), while the presently accepted phyla evolved between 358 and 541 MYA (Devonian–Cambrian). Divergence times for subphyla are generally between 358 and 485 MYA (Devonian–Ordovician), those of classes 145–358 MYA (Jurassic–Carboniferous), subclasses 66–358 MYA (Cretaceous–Carboniferous), orders 23–252 MYA (Paleogene–Triassic), families 2.8–145 MYA (Neogene–Cretaceous), and genera 2.8–66 MYA (Neogene–Paleogene). Thus, there are wide discrepancies in the times different taxa diverged. We provide an overview over Ascomycota, showing how application of temporal banding could affect the recognition of higher taxa at certain rank levels. We then use Sordariomycetes as an example where we use divergence times to provide additional evidence to stabilize ranking of taxa below class level. We propose a series of evolutionary periods that could be used as a guide to determine the various higher ranks of fungi: phyla  > 550 MYA, subphyla 400–550 MYA; classes 300–400 MYA; subclasses 250–300 MYA, orders 150–250 MYA, and families 50–150 MYA. It is proposed that classification schemes and ranking of taxa should, where possible, incorporate a polyphasic approach including phylogeny, phenotype, and estimate of divergence times.